Status Merokok dengan Kejadian Sindroma Koroner Akut (SKA) di Unit Perawatan Intensif RSI Jemursari Surabaya - Sabila, Danisa Nur; Riza, Mohammad Faishal (Riviera Publishing, 2025)
Acute coronary syndrome (AKS) is defined as a spectrum of conditions in patients who experience changes in new symptoms or clinical signs, with or without changes in the 12-stage electrocardiogram (ECG), and with or without an acute increase in cardiac troponin levels. The occurrence is based on various risk factors, both modification and non-modification. Atherosclerosis is the main pathophysiology of the occurrence of SKA due to smoking. The content in cigarettes gradually causes a decrease in NO production, blood vessels become stiff, and blood flow is disrupted, marking the beginning of endothelial dysfunction until symptoms of SKA appear. Methods: The type of research is observasional deskriptif, with cross-sectional studies and sampling techniques in total sampling. The subjects of the study were 57 patients with acute coronary syndrome who were treated in the ICU room of RSI Surabaya Jemursari for the period of January 2023 – December 2024. Observed variables, namely age, gender, smoking status and incidence of SKA Results and Discussion: Based on 57 total samples, most of the incidence of SKA is UAP type with 35 cases (71.9%), the majority are experienced by male 41 patients (71.9%) with an average age of 48–72 years (68%). Smoking status data on SKA patients was obtained by 35 patients (61.4%).